2018
DOI: 10.1038/s41560-017-0068-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial decoupling of light absorption and catalytic activity of Ni–Mo-loaded high-aspect-ratio silicon microwire photocathodes

Abstract: Substrates with arrays of silicon microwires (4 µ m diameter, 40 µ m length and 6 µ m pitch) with radial junctions (p-type base and 900 nm A solar-driven photoelectrochemical cell provides a promising approach to enable the large-scale conversion and storage of solar energy, but requires the use of Earth-abundant materials. Earth-abundant catalysts for the hydrogen evolution reaction, for example nickel-molybdenum (Ni-Mo), are generally opaque and require high mass loading to obtain high catalytic activity, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
153
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(160 citation statements)
references
References 32 publications
7
153
0
Order By: Relevance
“…Another approach to reducing parasitic light absorption of electrocatalysts is to minimize the geometric footprint of the opaque electrocatalysts on the light‐absorbing surfaces of semiconductors . Constructing three‐dimensional (3D) electrocatalysts on the surface of semiconductor photoelectrodes can relax the constraint on the catalyst loading against catalyst footprint, and therefore decouple the light absorption of semiconductor and surface charge transfer.…”
Section: Semiconductor/electrocatalyst Interfacementioning
confidence: 99%
See 2 more Smart Citations
“…Another approach to reducing parasitic light absorption of electrocatalysts is to minimize the geometric footprint of the opaque electrocatalysts on the light‐absorbing surfaces of semiconductors . Constructing three‐dimensional (3D) electrocatalysts on the surface of semiconductor photoelectrodes can relax the constraint on the catalyst loading against catalyst footprint, and therefore decouple the light absorption of semiconductor and surface charge transfer.…”
Section: Semiconductor/electrocatalyst Interfacementioning
confidence: 99%
“…d) Contour plot of the η IRC as a function of pitch and wire coverage for all tested combinations. Reproduced with permission . Copyright 2018, Springer Nature Publishing AG.…”
Section: Semiconductor/electrocatalyst Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…[50] Vijselaar et al found that photovoltaic current densities of silicon microwires with a radial p/n junction increase with increasing microwire spacing. [45] Our results show predominantly the same trend ( Figure 6.9) which indicates that underperformance of devices with a low microwire spacing might be due to limitations in light absorption. This is supported by the study of Chakthranont et al who published a similar concept as discussed in this chapter, after completion of our study, and obtained higher photocurrents in sulfite oxidation on microwire-structured samples than on flat equivalents.…”
Section: Light Absorption Propertiessupporting
confidence: 72%
“…[45] Their results strengthen our hypothesis of diffusion limitation of redox species in the internal volume of the microwire array, since in the cited study light trapping properties of the microwire structure were utilized without suffering from mass transfer inside the microwire array because of the placement of the catalyst at the top only.…”
Section: Mass Transfer Effectssupporting
confidence: 69%